Menggali Kesiapsiagaan Keluarga dalam Perencanaan Tanggap Darurat Bencana bagi Penyandang Disabilitas Mental di Indonesia: Exploring Family Preparedness in Response Planning Disaster Emergency for People with Mental Disabilities in Indonesia - Rika Sarfika; Ainul Fitri; Elvi Oktarina (NERS Jurnal Keperawatan, 2023)
Indonesia, as an archipelagic nation, faces a significant level of disaster vulnerability, with 3,721 natural disasters recorded in 2019. Vulnerable groups are one of the groups with the highest risk that need to be managed and given special attention in society, namely the disabled group. Disaster preparedness is an activity to minimize disaster risk, where preparedness is owned by anyone everywhere covering responding to disaster events quickly and effectively. The purpose of this study was to explore the preparedness of families with mental disabilities in disaster emergency response planning. A qualitative study was prepared using a phenomenological approach. A total of four participants who had family members with mental disabilities in Patient Nan Tigo Village participated in this study. Each participant was interviewed in depth to gather information regarding the participant's disaster emergency response plan for their family members with mental disabilities. The research results obtained 2 themes, namely: 1) Evacuation planning, and 2) Planning for family assistance and rescue. The results of this study provide recommendations that the family is the closest and trusted person for persons with mental disabilities, so that the ability and role of the family in disaster emergency response planning is very important to improve.